Measurement-Based Evaluation of Distribution Transformer Losses Characteristics for Sustainable Voltage Regulation - Korunovic, Lidija (Journal of Energy Technology, 2026)
This paper presents the characteristics of distribution transformer losses obtained on the basis of field measurements in a distribution grid. The active and reactive powers were recorded simultaneously at both 110 kV and 35 kV transformer voltage levels in different periods of the days, when the position of the on-load tap changer was changed intentionally. The variations of total transformer losses during these experiments were modelled by exponential models. The parameters of the models were grouped according to the particular daily periods, analysed statistically and compared with corresponding parameters of transformer load models. The importance was emphasised of knowing transformer losses characteristics in the networks with a significant share of distributed generation, energy storage systems and electric vehicles.